Analysis of thermal diffusion effects observed in a capacitively coupled plasma deposition reactor with non-isothermal walls. (May 2021) - Kim, Ho Jun
Abstract: In the semiconductor industry, non-isothermal wall conditions are often adopted to optimize process results for plasma enhanced chemical vapor deposition (PECVD). When heavier (or larger) species are mixed with lighter (or smaller) species in the presence of non-isothermal wall conditions, thermal diffusion phenomena are often observed. Thermal diffusion generates a concentration of the heavier (or larger) species in colder regions, while the lighter (or smaller) species are transported towards the hotter regions. Consequently, both averaged values and spatial profiles of film deposition rates can be noticeably changed by thermal diffusion. When uniformity of the deposition rate profile is required to be less than 5%, an accurate numerical model needs to involve complex multi-component transport. In this study selected input parameters, such as the mole fraction of a source gas, gas velocity magnitude, susceptor temperature, and gas pressure are varied to carefully investigate thermal diffusion effects on the spatial density distributions of ions and radicals. As a case study for PECVD, SiH4 /He capacitively coupled plasma is selected to deposit a hydrogenated amorphous silicon film. It is found that a sufficient increase of the susceptor temperature is best for obtaining a uniform deposition rate profile in the test bed. Highlights: We demonstrated thermal diffusion effects to plasma density distributions in PECVD. An accurate numerical model needs to involve complex multi-component transport. Thermal diffusion should be considered in modeling PECVD with non-isothermal walls. Thermal diffusion induces the heavier species to be transported to colder regions. We found that increase of substrate temperature is useful for uniform deposition.